(untitled) (Research, Society and Development, 2020)
The increased prevalence of obesity has highlighted this pathology, especially its consequences. This study aims to share an experience report of nursing students with the application of Nursing Care Systematization (NCS) to an obese young adult patient, with systemic arterial hypertension and umbilical hernia, during the Adult and Elderly Health discipline. After data collection and active listening of the patient, it was possible to elaborate the nursing diagnoses based on NANDA taxonomy (North American Nursing Diagnosis Association) and their respective interventions in order to find support to assist in the favorable prognosis of this patient, improve his quality of life and the student’s professional practice. It was concluded that the NCS is an essential tool for the provision of a quality care. Furthermore, it is possible to see the importance of practical classes and the experience report to the academic life of health students.